2018
DOI: 10.1051/e3sconf/20185701004
|View full text |Cite
|
Sign up to set email alerts
|

Kalman filter model, as a tool for short-term forecasting of solar potential: case of the Dakar site

Abstract: The prediction of solar potential is an important step toward the evaluation of PV plant production for the best energy planning. In this study, the discrete Kalman filter model was implemented for short-term solar resource forecasting one the Dakar site in Senegal. The model input parameters are constituted at a time t of the air temperature, the relative humidity and the global solar radiation. The expected output at time t+T is the global solar radiation. The model performance is evaluated with the square r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Energies 2021, 14, x FOR PEER REVIEW 4 of 29 of time series. Its effectiveness to predict solar radiation has been proven in several research works [17,20]. The AR presumes that each point can be predicted performing the p previous points and taking into account a random error term as presented in Equation (1).…”
Section: Solar Radiation Prediction Using the Arma Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Energies 2021, 14, x FOR PEER REVIEW 4 of 29 of time series. Its effectiveness to predict solar radiation has been proven in several research works [17,20]. The AR presumes that each point can be predicted performing the p previous points and taking into account a random error term as presented in Equation (1).…”
Section: Solar Radiation Prediction Using the Arma Modelmentioning
confidence: 99%
“…These good forecasting results have been explained by the convenience, the accurate prediction, and the simple computations which characterize the ARIMA model. ARMA has been the focus of several other studies [16,17], it was used in [16] to forecast the solar radiation and then compared with the persistence model. Simulation results have shown that ARMA outperforms the persistence model on the short and medium horizon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance was evaluated using four indicators that are widely used in the literature to evaluate the performance of forecasting models. These are: the root mean square error (RMSE), the normalized root mean square error (NRMSE), the mean absolute error (MAE), and the normalized mean absolute error (NMAE), as defined by Equations ( 3)-( 6) [65][66][67]:…”
Section: Performance Evaluationmentioning
confidence: 99%
“…To complete this limit, we propose forecasting models for short-term horizons from 30 minutes to 06 hours. Using Kalman filters, solar potential forecasting is carried out over a 20-minute horizon in Dakar [16] ; the results are obtained with a normal quadratic error of 4.8%. The works [17] studied short-term forecasting of solar potential in Dakar using the autoregressive moving average (ARMA) method; annual meteorological data from the "École Supérieure Polytechnique Dakar" were used; the results show a correlation coefficient of 0.97 and a root mean square error (RMSE) of 0.629.…”
Section: Introductionmentioning
confidence: 99%